Hubungan Pengetahuan Ibu Bersalin terhadap Sikap Inisiasi Menyusui Dini (IMD) di PMB Cynthia Purba Kecamatan Panei Kabupaten Simalungun - Jumrahwaty Parhusip; Ridesman Ridesman; Riska Susanti Pasaribu (Corona: Jurnal Ilmu Kesehatan Umum, Psikolog, Keperawatan dan Kebidanan, 2024)
Mobilization is a basic human need required by individuals to carry out daily activities in the form of joint movement, posture and gait in order to meet activity needs and maintain health. The World Health Organization (WHO) says that births by caesarean section are around 10-16% of all births in developing countries, in the last 30 years the incidence of caesarean sections has increased very rapidly, for many reasons but some also don't have the right reasons, just because the patient wants the operation or the doctor wants an easy way, in Australia around 16% to 20% of the reason for the high number of caesareans in the United States is because most obstetricians. The aim of the research was to analyze the relationship between early mobilization post cesarean section and the surgical wound healing process in the postpartum room at Kartika Pulomas Hospital. The type of research used is qualitative analytic with a cross sectional approach design. The sampling technique uses accidental sampling. The number of samples used was 61 people. There is a relationship between early mobilization post cesarean section and the surgical wound healing process in the postpartum room at Kartika Pulomas Hospital. The paired sample t-test showed a value of p = 0.002, meaning p<0.05. Recommendations for hospitals need to have a policy for early mobilization of patients after caesarean section. Early mobilization accelerates wound healing and shortens the period of hospital treatment, so that it is a promotion for the hospital, namely: establishing independent hospitals as the main choice with quality services.